2013
DOI: 10.1371/journal.pone.0079968
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Glucose-Lowering Agents on the Risk of Cancer in Type 2 Diabetic Patients. The Barcelona Case-Control Study

Abstract: BackgroundThe aim of the present study is to evaluate the impact of glucose-lowering agents in the risk of cancer in a large type 2 diabetic population.MethodsA nested case-control study was conducted within a defined cohort (275,164 type 2 diabetic patients attending 16 Primary Health Care Centers of Barcelona). Cases (n = 1,040) comprised those subjects with any cancer diagnosed between 2008 and 2010, registered at the Cancer Registry of Hospital Vall d'Hebron (Barcelona). Three control subjects for each cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 46 publications
1
35
0
3
Order By: Relevance
“…1 and Supplementary Fig. 2) (5,8,(14)(15)(16)(17)(19)(20)(21)23,25,26,28). Four of 13 studies reported an association of insulin glargine and breast cancer (8,19,21,24).…”
Section: Study Characteristics and Effect Estimatesmentioning
confidence: 99%
See 4 more Smart Citations
“…1 and Supplementary Fig. 2) (5,8,(14)(15)(16)(17)(19)(20)(21)23,25,26,28). Four of 13 studies reported an association of insulin glargine and breast cancer (8,19,21,24).…”
Section: Study Characteristics and Effect Estimatesmentioning
confidence: 99%
“…1). Following our inclusion criteria, 16 cohort and 3 case-control studies were included in this systematic review (5)(6)(7)(8)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). All studies evaluated insulin glargine, with four studies also investigating insulin detemir (15,17,25,28).…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations